THE USE OF GOOLE FORM AS A LEARNING EVALUATION TOOL IN ENGLISH LESSONS DURING PANDEMIC COVID-19 - Hanafi Wibowo; Arli Adinda Rahmah (Akademika : Jurnal Teknologi Pendidikan, 2021)
The purpose of this study was to describe online English learning activities, describe the implementation of online English activities, and find out the implementation of online English learning activities carried out in class VIII of SMP Negeri 168 Jakarta during the Covid-19 pandemic. This sample determination used a random sampling technique, where there are three students of class VIII SMPN 168 Jakarta, with a total of 108 students. The research method used in this research is descriptive research. The results showed that the application of the google form application assisted by whatsapp as a means of giving gifts,providing information, submitting assignments, collecting student assignments, and recapitulating student scores. Learning activities took place effectively with the percentage of students participating in online activities 98.04%. Assessment of English in online learning was compiled using the Googleform application on the first and second online. data Based on the assessments made from the first and second online, the average score of students' English is 77.31 and the percentage of students whose learning outcomes exceed the KKM is 75.15%. So it can be said that the implementation of online learning in class VIII SMPN 168 Jakarta is effective.